Dread Nation: Dread Nation #1 - Ireland, Justina (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
When families go missing in Baltimore County, Jane McKeene, who is studying to become an Attendant, finds herself in the middle of a conspiracy that has her fighting for her life against powerful enemies.
Keywords: Horror stories; Conspiracies -- Fiction; Zombies -- Fiction; African Americans -- Fiction; Conspiracies -- Fiction; Zombies -- Fiction; African Americans -- Fiction; Horror fiction